1989
DOI: 10.1038/bjc.1989.237
|View full text |Cite
|
Sign up to set email alerts
|

LHRH agonists and the prevention of breast and ovarian cancer

Abstract: S_minary Early age at natural menopause or bilateral ovanrectomy substantially reduce a woman's lifetime nsk of breast cancer. Reversible 'bilateral ovariectomy' can now in effect be achieved by 'high-dose' luteinising hormone releasing hormone (LHRH) agonists (LHRHAs). The harmful effects of such medical reversible bilateral ovariectomy, in particular the increased risks of coronary heart disease and osteoporosis, can in all likelihood be obviated by 'low-dose' oestrogen replacement therapy (ERT), specificall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 31 publications
0
18
0
1
Order By: Relevance
“…We have suggested (Pike et al, 1989;Spicer et al, 1991) that chemoprevention of breast cancer in young premenopausal women could be achieved by a contraception approach in which ovulation is inhibited by the use of a gonadotropin releasing hormone analog (GnRHA). Use of a GnRHA to block ovulation permits the add-back dose of estrogen and progestin to be selected purely on the basis of providing protection from the hypoestrogenism induced by blocking ovulation and the need to protect the endometrium; we suggested that a dose of estrogen equivalent to that used in ET with very intermittent progestin (10-12 days every 4 months) would provide such protection.…”
Section: Chemoprevention With 'Antihormonal' Drugsmentioning
confidence: 99%
“…We have suggested (Pike et al, 1989;Spicer et al, 1991) that chemoprevention of breast cancer in young premenopausal women could be achieved by a contraception approach in which ovulation is inhibited by the use of a gonadotropin releasing hormone analog (GnRHA). Use of a GnRHA to block ovulation permits the add-back dose of estrogen and progestin to be selected purely on the basis of providing protection from the hypoestrogenism induced by blocking ovulation and the need to protect the endometrium; we suggested that a dose of estrogen equivalent to that used in ET with very intermittent progestin (10-12 days every 4 months) would provide such protection.…”
Section: Chemoprevention With 'Antihormonal' Drugsmentioning
confidence: 99%
“…The concept is largely based on the epidemiological observations that an early age of natural menopause or early oophorectomy for reasons other than breast cancer, substantially reduces the incidence of the disease (Pike et al, 1989). Currently tamoxifen is the most likely candidate for such a prophylactic regime, since the antioestrogen has not only proven effectiveness in both primary (SBCT report, 1987;Nato report, 1990) and advanced (Patterson et al, 1981;Furr & Jordan, 1984) breast cancer, but also shows a low incidence of side-effects.…”
mentioning
confidence: 99%
“…Plusieurs auteurs ont avancĂ© l'idĂ©e d'un effet potentiellement protecteur des analogues de la GnRH vis-Ă -vis du cancer de l'ovaire [29,30]. Hormis un phĂ©nomĂšne de blocage de l'ovulation, plusieurs Ă©lĂ©ments pourraient expliquer cet effet protecteur des analogues du GnRH.…”
Section: Analogues De La Gnrhunclassified